Effects of a fantasy activity in therapeutic interaction measures (Brazilian Journal of Behavioral and Cognitive Therapy, 2013)
The aim of this article is to report a study that has evaluated the effects of a fantasy activity on client-therapist interaction. Ten sessions of a behavioral analysis therapy process were recorded on video, transcripted and coded. Independent coders were trained until reached the agreement criterion. The fantasy activity was introduced on the condition B in a ABABA design. There was decrease on the categories titled Report Request and Reflection Request, and increase on the Interpretation, Information and Recommendation. There were increase in Establishing Relationship Between Events and decrease of Events Reporting. The expressive increase in the reporting of goals and improvements by the client at the sessions following the condition B were discussed. Studies were suggested to clarify the effect of the therapist interventions. Additionally, it was suggested the investigation of the accurate contingent descriptions and the reports about improvement and clinical changes.
Keywords: fantasy activity; therapist/client interaction; clinical behavior analysis